Association between nut consumption and cancer risk: a meta-analysis. (13th December 2022) - Cao, Chang; Gan, Xinyan; He, Yan; Nong, Shiqi; Su, Yonglin; Liu, Zheran; Zhang, Yu; Hu, Xiaolin; Peng, Xingchen
Abstract: This study aims to conduct a meta-analysis and dose-response analysis of the relationship between nut intake and cancer risk and mortality. Electronic databases were searched. A meta-analysis was conducted to calculate the pooled effect sizes (ESs) with the corresponding 95% CIs, and a dose-response analysis was performed. A random-effects model was used in the statistical analysis. Two independent reviewers completed the full-text screening, data extraction, and quality assessment. We included 17 articles in the present meta-analysis. Total nuts intake was revealed to be significantly associated with reduced cancer risk (ES: 0.9; 95% CI: 0.86–0.95; P  < 0.001) and cancer mortality (ES: 0.88; 95% CI: 0.85–0.92, P  < 0.001), especially lung cancer risk (ES: 0.86; 95% CI: 0.81–0.91, P  < 0.001) and gastric cancer risk (ES: 0.79; 95% CI: 0.68–0.91, P  = 0.001). Moreover, a 10 g/d increment of tree nuts consumption was associated with a 20% cancer mortality reduction (ES: 0.80; 95% CI: 0.71–0.89; P  < 0.0001). Nuts intake is significantly associated with the reduction of cancer risk and mortality. Especially, nuts intake is significantly associated with reduced lung cancer risk and gastric cancer risk. Noticeably, a 10 g/d increase in tree nuts intake is related to a 20% reduction in overall cancer mortality.